The Analysis of Stigmatisation and Community Acceptance in Malang City towards Wolbachia-infected Aedes aegypti in Dengue Fever Vector Control - Jenvia Rista Pratiwi; Noventia Sekar Pratiwi; Ridwan Muhamad Rifai; Ghea Pratiwi Santoso; Hanifa Salsabila; Anie Yulistyorini (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Dengue fever is a top ten global health threat according to the World Health Organisation (WHO). Indonesia, especially Malang City has 560 dengue haemorrhagic fever cases in 2022 with Sukun Sub-district having the highest number of 159 cases. Dengue haemorrhagic fever vector control carried out by the government is currently 3M (drain, cover, and recycle) where it is still conventional. Whereas generally now there have been many studies on dengue vector control innovations, one of which is the Ae. aegypti with Wolbachia. The programme has been implemented in Yogyakarta and resulted in a decrease in dengue fever cases. The purpose of this study was to analyse the stigma and acceptance of the community in Malang City towards the Wolbachia-infected Ae. aegypti with Wolbachia programme in controlling dengue haemorrhagic fever vector. Methods: The method used was cross-sectional using questionnaires to 100 communities in Sukun Sub-district, Malang City with non-dense and dense populations. Results: The results showed that 87.5% of densely populated communities were aware of the programme, while only 5% of non-densely populated communities were aware of the programme. Based on the questionnaire results, it is known that the majority of community concerns about the programme between non-dense and dense communities are the same, namely the cost and health risks. However, after distributing the comic